Boosting bonding strength of hydroxyapatite coating for carbon/carbon composites via applying tree-planting interface structure. Issue 9 (1st May 2021) - Liu, Yeye; Zhang, Leilei; Guan, Kejie; Wang, Zhongkai; Wang, Yuting; Li, Huapeng; Lei, Xinying; Zhang, Weixi; Wang, Ke; Hu, Yiyao
Abstract: Hydroxyapatite (HA) coated carbon/carbon composites (CC) is a potential material for orthopedic application because of the combination of good biocompatibility and mechanical properties. In this work, we synthesize a tree-planting interface which is composed of holes formed by micro-oxidized CC substrates and carbon nanotubes (CNTs) to achieve a high bonding strength of HA coating. The holes include annular gaps between carbon fiber and pyrolytic carbon, as well as irregular holes formed by oxidized pyrolytic carbon. The CNTs can grow inside the holes and extend into the HA coating. As a result, the bonding strength of HA coating with tree-planting interface achieves 11.14 ± 0.78 MPa. It increases by 181.3% comparing with the HA coating on CC without interface (3.96 ± 0.30 MPa). The in-vitro bioactivity evaluated by the response of mesenchymal stem cells (MSCs) shows promotions of cell proliferation and cell activity with increasing culture time. After applied with tree-planting interface, the HA coating with strong bonding and good bioactivity may be applied in orthopedic field in the future.